Panchromatic sensitizer for dye-sensitized solar cells: un-symmetrical squaraine dyes incorporating benzodithiophene π-spacer with alkyl chains to extend conjugation, control the dye assembly on TiO2 and retard charge recombination - Bisht, Rajesh; Munavvar, Fairoos Mk; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (Journal of Organic Chemistry, 2017)
Metal-free near-infrared (NIR) active unsymmetrical squaraine dyes, RSQ1 and RSQ2, with benzodithiophene (BDT) π-spacer and cyanoacrylic acid acceptor were synthesized by utilizing palladium catalyzed direct (hetero)arylation reaction. Methyl and 2-ethylhexyl groups were strategically placed at the BDT unit for RSQ1 and RSQ2 respectively, to investigate the effect of alkylated π-spacer on dye aggregation on the TiO2 surface and recombination reactions at TiO2/dye/electrolyte interface. These dyes have strong absorption ( ε>10(5) M(-1)cm(-1)) in near-infra red (NIR) region and exhibit similar optical and electrochemical properties as they have same conjugated framework. RSQ2 performed better than RSQ1 owing to its higher open-circuit voltage (Voc) and fill factor (ff) in spite of having comparable short-circuit current density (Jsc). The panchromatic incident photon-to-current conversion efficiency (IPCE) response was also observed for both the dyes. RSQ2 showed power conversion efficiency (PCE) of 6.72% with short-circuit current density (Jsc) of 18.53 mA/cm(2), open circuit voltage (Voc) of 0.538 V, and fill factor (ff) of 67.4%, without any co-adsorbent. Attenuation of the charge recombination for RSQ2 was revealed by electrochemical impedance analysis (EIS) and open-circuit potential decay transients (OCVD), which attributes to its higher Voc and ff in comparison to RSQ1.

Fused fluorenylindolenine-donor-based unsymmetrical squaraine dyes for dye-sensitized solar cells - Bisht, Rajesh; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Karjule, Neeta; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
A series of four unsymmetrical squaraine dyes, XSQ1-4, were synthesized using a fused fluorenylindolenine-based donor unit for dye-sensitized solar cells (DSSCs). The fused structure of fluorenylindolenine helped in moving the absorption toward the near-infrared (NIR) region, and the two sp(3)-C centers available on this donor were utilized to incorporate out-of-plane alkyl chains in opposite directions to control the dye-dye interactions on the TiO2 surface. High extinction coefficient (epsilon >= 10(5) M-1 cm(-1)) for absorbing NIR photons and suitable highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with respect to the conduction band of TiO2 and electrolyte for charge injection and dye regeneration processes, respectively, make these dyes potential sensitizers for DSSCs. Introduction of branched alkyl groups in the pi-framework helped in controlling dye aggregation to reduce exciton quenching and assisted in TiO2 surface passivation to avoid the charge recombination process. Furthermore, having a naphthyl group on the indole part of the anchoring group containing segment helped to red-shift the absorption spectrum of dyes 15 nm toward the NIR region (XSQ3-4). Among all of the dyes under investigation, XSQ2 gave the best photovoltaic performance, having a short-circuit current density (J(SC)) of 13.99 mA cm(-2), open -circuit voltage (V-OC) of 0.66 V, and a fill factor (ff) of 0.71, with a device performance (eta) of 6.57%. Electrochemical impedance spectroscopy revealed higher electron lifetime on TiO2 for XSQ2, which helps to avoid the charge recombination process.
Keywords: Dye-sensitized solar cells; fluorenylindolenine; H- and J-type aggregation; NIR absorption; out-of-plane alkyl groups; squaraine dyes

Indenoquinaldine-based unsymmetrical squaraine dyes for near-infrared absorption: investigating the steric and electronic effects in dye-sensitized solar cells - Bisht, Rajesh; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Chemistry-A European Journal, 2018)
A series of near-infrared (NIR)-responsive unsymmetrical squaraine dyes (ISQ1-3) incorporating a fused indenoquinaldine-based donor have been designed and synthesized. C-12 alkyl chains were incorporated at the sp(3)-hybridized carbon center of the indene unit of the indenoquinaldine in an out-of-plane orientation to control dye aggregation on the surface of titanium dioxide, and indole (ISQ1), benzo[e]indole (ISQ2), and quinoline (ISQ3) moieties were included as the donor component bearing the anchoring carboxy group to extend the absorption in the NIR region and to systematically study the effect of the electronic modification on the performance of dye-sensitized solar cells (DSSC). All the dyes exhibit intense absorption (epsilon >= 10(5) m(-1) cm(-1)) in the NIR region, and the dye-adsorbed TiO2 films exhibit broad panchromatic absorption. The incident photon-to-current efficiency (IPCE) spectrum of the ISQ3-based DSSC device displays a panchromatic IPCE response up to 880 nm. Additionally, the ISQ3-sensitized device provides the best efficiency of 4.15% with a short circuit current density (J(SC)) of 10.02 mA cm(-2), open-circuit voltage (V-OC) of 0.58V, and fill factor (ff) of 72% in the presence of 10 equivalents of 3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid (CDCA). Electrochemical impedance spectroscopy analysis showed attenuated charge recombination in the ISQ3-sensitized DSSC, which contributes to its higher value of V-OC compared with the other dyes.

Modulated photochemical reactivities of O-acetylated (3', 5'-dimethoxyphenyl) heteroaryl acyloin derivatives under direct irradiation and photo-induced electron transfer conditions - Bisht, Rajesh; Singh, Saumya; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemical & Photobiological Sciences, 2018)
3', 5'-Dimethoxybenzoin esters are important photoremovable protecting groups which form 2-phenylbenzofuran derivatives upon photo-release. We utilized a similar concept to test a photochemical method of installing a benzofuran moiety to the conjugated backbone by subjecting O-acetylated (3', 5'-dimethylphenyl) heteroaryl acyloin derivatives through direct photo irradiation and a photo-induced electron transfer reaction. These photochemical methods were explored for a variety of heteroaromatic substrates appended on the ketone part of the O-acetylated cross-acyloin derivatives. The furan, thiophene and bithiophene derivatives led to the expected cyclized (benzofuran capped) products but the derivatives with extended conjugation decomposed under direct irradiation. However, under irradiation in the presence of an electron donor such as triethylamine, the extended acyloin derivatives afforded both cyclized and deacetoxylated products. The semiconducting nature of the extended cyclized products was also explored and tested for solution-processed organic field effect transistors, providing a maximum hole mobility of 1.3 x 10(-6) cm(2) V-1 s(-1).

Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Modular TiO2-squaraine dyes/electrolyte interface for dye-sensitized solar cells with cobalt electrolyte - Singh, Ambarish Kumar; Sudhakar, Vediappan; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2023)
Strategies to diminish both charge recombination and aggregation of dyes on the photoanode by functionalizing the sensitizer with alkyl groups is the best approach to achieve high dyesensitized solar cell (DSSC) efficiency. Development of such a photoanode with NIR-active dyes which is compatible with a cobalt electrolyte is important to enhance the photovoltaic performance. In this report, alkyl-group-wrapped donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been used for DSSC device characterization with a cobalt electrolyte. Surface passivation of photoanode was varied systematically by the extent of functionalization with alkyl groups to avoid charge recombination. DSSC device performance of 5.92% was achieved for an alkyl-group-wrapped squaraine dye with a cobalt electrolyte. Hence, appending the alkyl groups on the donor unit of squaraine dyes helps passivating the photoanode, whereas introducing hydrophilic groups provides a leaky surface where oxidized electrolyte species reach the titanium-metal-oxide surface which promotes the charge recombination process.
Keywords: counter-electrode; DSSC device efficiency; Dye-sensitized solar cells; Electrolytes; unsymmetrical squaraine dye